Analyzing STEM Students’ Critical Thinking Performance: Literacy Study on the Polymer Film Fabrication Process Irradiated with Gamma Rays - Bilad, Muhammad Roil; Doyan, Aris; Susilawati, Susilawati (International Journal of Essential Competencies in Education, 2022)
The reliability of pedagogical practice is highly dictated by how it enhances science, technology, engineering, and mathematics (STEM) students’ critical thinking achievement. Adequate pedagogical practice is thus needed in line with the demands of STEM learning in the 21st century, namely achieving optimal critical thinking. This paper reports this pedagogical practice on a topic of polymer film fabrication irradiated with gamma rays. The specific objective was to analyze STEM students’ critical thinking performance in literacy of the aforementioned topic. It is an exploratory study with an experimental method. Only one treatment group was involved, they were STEM students attending the Material Physics Courses. By employing valid critical thinking instruments and adequate methods of analysis, the findings show that literacy on the assigned topic significantly improved STEM students’ CT skills. It was proven that the mean scores of CT indicators have increased in all aspects of the CT assessed. The statistical analysis confirmed that there were significant differences in the CT skills of STEM students between the observations before and after the learning process intervention. The implication of this study is that pedagogical interventions integrated with studies on advanced material modification technology could be effectively used for creating inspiring STEM learning, especially for training STEM students’ critical thinking ways.